Influence of nutritional status on clinical outcomes in critically ill children - K. M., Chaitra; G., Bhavya; S., Harish; Patel, Shruthi; Anjum, Syeda Kausar (International Journal of Contemporary Pediatrics, 2018)
Background: Critically-ill children have a state of metabolic stress. The nutritional needs of these patients can be increased. Their nutritional status at admission and its possible deterioration during hospitalization can be a predictor of worse outcome. The objective of this study was to study the influence of nutritional status on outcomes like mortality, duration of mechanical ventilation and duration PICU stay and hospital stay, in critically ill children. Methods: This was a prospective comparative study conducted on 60 critically ill children aged 1 month to 18 years admitted to PICU of tertiary care, teaching hospital, Bangalore, Karnataka over a study period of 12 months. Patients were divided into 4 categories based on Body mass index (BMI) as per WHO growth charts into: underweight, normal, overweight and obese and outcomes was analysed. Results: In the present study 60 children were studied. Subjects were classified as underweight (23.33%), normal weight (45%), overweight/obese (31.67%) based on BMI Z-score at admission. The odds of prolonged hospital stay were higher in underweight and overweight/obese children (OR-2.85, p-0.12 and OR-3.92, p-0.03 respectively). Underweight and overweight/ obese children had higher odds for prolonged PICU stay. (OR-6, p-0.02 and OR-2.13, p-0.36 respectively). Underweight children required prolonged ventilator support (OR-2, p-0.03). There was no significant difference among the group. Conclusions: There is a high prevalence of malnourishment in critically ill children compared to general population and they are prone for poor outcome. Malnourished children must be identified at admission and optimal therapies, nutritional strategies aimed at preventing further nutritional deterioration should be made.